Reduction in femoral neck and total hip bone mineral density following hospitalisation for diabetes-related foot ulceration - Marcel M. Nejatian (Nature Portfolio, 2021)
Abstract Management of diabetes-related foot ulceration (DFU) includes pressure offloading resulting in a period of reduced activity. The metabolic effects of this are unknown. This study aims to investigate changes in bone mineral density (BMD) and body composition 12 weeks after hospitalisation for DFU. A longitudinal, prospective, observational study of 22 people hospitalised for DFU was conducted. Total body, lumbar spine, hip and forearm BMD, and total lean and fat mass were measured by dual-energy X-ray absorptiometry (DXA) during and 12 weeks after hospitalisation for DFU. Significant losses in total hip BMD of the ipsilateral limb (− 1.7%, p < 0.001), total hip BMD of the contralateral limb (− 1.4%, p = 0.005), femoral neck BMD of the ipsilateral limb (− 2.8%, p < 0.001) and femoral neck BMD of the contralateral limb (− 2.2%, p = 0.008) were observed after 12 weeks. Lumbar spine and forearm BMD were unchanged. HbA1c improved from 75 mmol/mol (9.2%) to 64 mmol/mol (8.0%) (p = 0.002). No significant changes to lean and fat mass were demonstrated. Total hip and femoral neck BMD decreased bilaterally 12 weeks after hospitalisation for DFU. Future research is required to confirm the persistence and clinical implications of these losses.